4-[(2,4-Dichlorophenyl)carbamoyl]butanoic Acid - Hanifa, B.; Sirajuddin, M.; Ullah, Z.; Sumera, M.; Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (MDPI, 2021)
The synthesis and spectroscopic characterization of the glutaric acid-amide derivative, 2,4-Cl2C6H3N(H)C(=O)(CH2)3C(=O)OH (1), are described. The X-ray crystal structure determination of (1) shows the backbone of the molecule to be kinked about the methylene-C–N(amide) bond as seen in the C(p)–N–C(m)–C(m) torsion angle of −157.0(2)°; m = methylene and p = phenyl. An additional twist in the molecule is noted between the amide and phenyl groups as reflected in the C(m)–N–C(p)–C(p) torsion angle of 138.2(2)°. The most prominent feature of the molecular packing is the formation of supramolecular tapes assembled through carboxylic acid-O–H…O(carbonyl) and amide-N–H…O(amide) hydrogen bonding.